The Role of Teachers’ Support and Enthusiasm in Predicting Mathematics Anxiety and Confidence among Students - Vidić, Tomislava; Klasnić, Irena; Đuranović, Marina (Revija za elementarno izobraževanje, 2022)
The goal of this study was to examine the contribution of teachers’ support and enthusiasm to explaining self-confidence and mathematics anxiety in primary-school students. The results of the t-test showed that girls and boys statistically significantly differ only in the perception of confidence variable, while no gender difference was determined in the other variables. The results of regression analysis showed that teachers' support and enthusiasm are predictors of student self-confidence, with support also making an independent contribution to explaining mathematics anxiety.